Study of important moulds isolated from milk and its products in Baghdad – with experimental study the pathogenesis of Aspergillus Fumigatus moulds in mice - Al-Kaisie, Bushra I.; Khalid, Jinan (The Iraqi Journal of Veterinary Medicine, 2005)
This study was designed to isolate and identify the type of moulds and theirpercentage of distribution with pathological study of highly moulds isolated from(130)samples were included in this study with divided into (30)samples driedmilk,(30).samples baby food ,(30)samples raw milk , (40) samples dairy products .The results revealed the percentage of infection according to total count ofisolation in raw milk were 100 % dairy product 65 %. The most common fungiisolated from raw milk were Asp.niger of 16.2 % Asp. fumigatus of 15 % Asp.flavusof 13.7 % Pencillium spp. 12.5 % . From dairy products were isolated withpercentage of Asp. Fumigatus 34.9% Geotrichum spp . of 23 % ,Asp. nager of 11.5% . Pathological study was carried out to investigate the clinical signs with grosslyand Histopathological changes inoculated with most pathogenic moulds Asp.fumigatus (30)male white swiss mice were used in this study and divided into fourgroups . The first group were injected I/P with 0.2 ml of Asp. fumigatus containing1X105 spores / ml , 4th group (control)given orally 0.2 ml of PBs.Two mice fromeach treated groups and one from each control group were scarified on week (1,2,3,4).the clinical manifestation of the 1st group were at 2nd week showed dyspnea .Mouldisolated from blood and internal organs at third week , with no isolation from 3rdgroup. The Histopathological observations showed presence of degeneration ,necrosis and diffused granuloma in liver, lung , spleen , kidney and hemorrhage withthrombosis in brain and intestine .